GENERIC SOCIAL MEDIA STRATEGIES BASED ON THE PROFILES OF THE UK SOCIAL MEDIA USERS - Mochtar, Marvilano (Digital Repository of Theses - SSBM Geneva, 2022)
As the COVID-19 pandemic has accelerated the great shift to online shopping in the UK, many UK B2C companies are now interested in developing their social media strategy. Unfortunately, there is a research gap in understanding the UK’s social media users and generic social media strategies that a UK-oriented B2C company can quickly adapt. Therefore, there is a need for a better understanding of the UK’s social media users to develop an effective social media strategy. Hence, this study: i) profiles the UK social media users; ii) provides a guide on the odds of adopting particular social media platforms based on consumers’ demographic and behavioral attributes; and iii) proposes a set of generic social media strategies that B2C companies can quickly adopt. This research will help many B2C firms in the UK engage their target customers better on social media.